Evolution of neocortical folding: A phylogenetic comparative analysis of MRI from 34 primate species. (September 2019) - Heuer, Katja; Gulban, Omer Faruk; Bazin, Pierre-Louis; Osoianu, Anastasia; Valabregue, Romain; Santin, Mathieu; Herbin, Marc; Toro, Roberto
Abstract: We conducted a comparative analysis of primate cerebral size and neocortical folding using magnetic resonance imaging data from 65 individuals belonging to 34 different species. We measured several neocortical folding parameters and studied their evolution using phylogenetic comparative methods. Our results suggest that the most likely model for neuroanatomical evolution is one where differences appear randomly (the Brownian Motion model), however, alternative models cannot be completely ruled out. We present estimations of the ancestral primate phenotypes as well as estimations of the rates of phenotypic change. Based on the Brownian Motion model, the common ancestor of primates may have had a folded cerebrum similar to that of a small lemur such as the aye-aye. Finally, we observed a non-linear relationship between fold wavelength and fold depth with cerebral volume. In particular, gyrencephalic primate neocortices across different groups exhibited a strikingly stable fold wavelength of about 12 mm (±20%), despite a 20-fold variation in cerebral volume. We discuss our results in the context of current theories of neocortical folding.